DATA RETENTION IN CJEU CASE LAW - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Possession of accurate, complete and reliable relevant data on electronic communications traffic and timely access of authorized competent state bodies to such data is without a doubt a useful tool in the fight against modern forms of crime. For that reason, it is justified to establish an obligation for providers of electronic communications services to keep certain data on communications for a certain period of time in the realization of which they mediate and to hand over that data at the request of authorized state bodies, in order to use them for legitimate purposes. For this reason, the Data Retention Directive was adopted in 2006, which Member States were required to transpose into national law. However, data retention poses a risk to basic human rights and freedoms, if the regulation establishing this obligation does so without respecting the essence of these rights and freedoms, especially the right to privacy and rights related to the processing of personal data, for which reason the Court of Justice of the European Union declared the Directive invalid is 2014. Despite this decision, Member States continue to regulate the obligation to retain data in their national regulations. In this regard, the question of compliance of these regulations with the fundamental rights and freedoms and principles of the Union is raised. The subject of the paper is the analysis of the case law of the Court of Justice of the EU on this issue after the annulment of the Data Retention Directive.
Keywords: criminal procedure, data retention, European Union, CJEU